2018
DOI: 10.1111/1744-9987.12697
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Intensive Granulocyte and Monocyte Adsorptive Apheresis Plus Ustekinumab in Patients With Refractory Crohn's Disease

Abstract: Ustekinumab is applied to induce clinical remission in patients with Crohn's disease. Granulocyte and monocyte absorptive apheresis depletes activated myeloid lineage leukocytes and has been applied for active Crohn's disease. This study retrospectively examined the efficacy and safety of combining intensive granulocyte and monocyte absorptive apheresis and ustekinumab for remission induction therapy in refractory Crohn's disease. Between June and September 2017, three consecutive cases (two females) with refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The mean endoscopic subscore was significantly lower at 10 weeks than at baseline. Based on these outcomes, addition of intensive GMA to TOF monotherapy appeared to be effective in inducing mucosal healing [17,18]. An additional study on a large cohort of patients is warranted to verify this finding.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The mean endoscopic subscore was significantly lower at 10 weeks than at baseline. Based on these outcomes, addition of intensive GMA to TOF monotherapy appeared to be effective in inducing mucosal healing [17,18]. An additional study on a large cohort of patients is warranted to verify this finding.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, in patients with active UC, downregulation of the leukocyte adhesion molecule Lselectin and neutrophil adhesion to endothelial cells activated by IL-1β were observed after in vitro exposure of peripheral blood to G-1 beads that composed a main part of Adacolumn [16]. These suggested that the combination therapy worked by drastically downregulating the circulating inflammatory cytokines and the expressions of adhesive molecules on the activated granulocytes, which was an effect of GMA, and by downregulating the local inflammatory cytokines at the microenvironmental sites in the gut mucosa, which was an effect of TOF, thereby, inducing rapid clinical remission [17,18]. In addition, serious adverse side effects have been rare in patients receiving GMA [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an in vitro study observed that the concentration of soluble cell adhesion molecule-1 and soluble vascular cell adhesion molecule-1 in blood samples was significantly reduced after GMs adsorption with acetate beads [ 9 ]. Such findings suggest that the present combination therapy suppressed leukocyte migration by drastically downregulating circulating inflammatory cytokines and expression of leukocyte-related adhesion molecules as an effect of GMA, and by downregulating local inflammatory cytokines at microenvironmental sites in the gut mucosa, as an effect of UST, thereby inducing rapid CR [ 12 , 13 ]. In addition, serious adverse side effects appear rare in patients receiving GMA [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies include eight studies evaluating combination therapy with GMA or LCAP and anti-TNF-α (IFX: 6 studies; ADA: 1 study; IFX, ADA, golimumab: 1 study), four studies with GMA and VDZ, one study with GMA and ustekinumab, and one exceptional study with GMA and a pan-JAK inhibitor tofacitinib. Among these 14 studies, seven studies[ 42 , 44 , 45 , 47 - 50 ] examined the efficacy of combination therapies in patients with UC, five studies[ 38 - 41 , 46 ] examined its efficacy for CD patients, and two studies[ 43 , 51 ] examined its efficacy for both UC and CD patients.…”
Section: Efficacy Of Combination Therapy With Cap and Biologics In Ib...mentioning
confidence: 99%
“…In addition, Motoya et al [ 52 ] showed that the incidence of AEs among elderly patients was similar in all patients. Regarding the safety of the combination therapy with CAP and biologics, eight out of 14 studies listed in Table 3 reported the rate of AEs[ 39 , 41 , 44 , 46 - 48 , 50 , 51 ]. Six of the eight studies reported no adverse events.…”
Section: Efficacy Of Combination Therapy With Cap and Biologics In Ib...mentioning
confidence: 99%